Fabrication of chiral networks for a tri-substituted anthraquinone derivative using molecular self-assembly. Issue 19 (29th April 2016) - Hu, Yi; Miao, Kai; Zha, Bao; Xu, Li; Miao, Xinrui; Deng, Wenli
Abstract : This work displays the fabrication of chiral networks which are induced by the dipole–dipole interaction and alkyl chain interdigitation. Abstract : Chiral structures are recorded, with the adsorption of an achiral anthraquinone derivative and co-adsorption of achiral solvent on an achiral surface. Dimer, trimer and tetramer aggregations are observed while only the tetramer–dimer combination constructs the whole monolayer, and the formation mechanism is explained from the thermodynamic and kinetic viewpoints.